Epidemiological profile of acquired syphilis in children and adolescents in Brazil: a nationwide observational study - Silva, Gabrielle Oliveira; Barbosa, Amanda Souza; Ferreira, Catarina David Rodamilans; Macedo Pinto, Igor; David Ferreira, Bárbara Simone (Frontiers in Pediatrics, 2026)
Acquired syphilis, which is historically considered a condition with almost exclusive prevalence in adults, has shown, in recent evidence, an alarming increase amongst the pediatric population. The objective of this study is to analyze and compare the time trends and epidemiological profile of acquired syphilis in the Brazilian population from ages 0 to 19 from 2015 to 2023. It consists of a descriptive, ecological study that utilizes secondary data from the Notifiable Health Conditions Information System (SINAN). The trend analysis used Joinpoint regression to calculate the Annual Percent Change (APC). From 2015 to 2023, 135,699 cases of acquired syphilis were registered in the age group studies, with 78.5% of confirmed cases and a concentration of 94.1% in the 15–19 age group. The results suggest a complex epidemiological scene, with the advancement of syphilis in various groups within the young population, evidencing the urgent necessity to strengthen prevention, diagnosis, and surveillance policies.